Pemberdayaan Perempuan Melalui Pendampingan Keikutsertaan KB Pada Pasangan Usia Subur Di Desa Bukit Suban Kabupaten Sarolangun - Asparian; Lia Nurdini; Sri Astuti Siregar; Puspita Sari (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
Suku Anak Dalam (SAD) is an indigenous community that lives in seclusion in the lowland forest with a seminomadic lifestyle and utilizes natural products to survive. In a society that adheres to patriarchal views, women tend to be powerless in making decisions, one of which is the decision to participate in family planning. Lack of knowledge, education, and the low economic level of SAD women makes it necessary to empower SAD women.The family planning program is one of the programs promoted by the government to increase the empowerment of women of childbearing age in the SAD community. Empowering women through family planning assistance should be a top priority in empowering this community to reduce population growth. The purpose of this intervention is to increase the knowledge, attitudes and skills of women of childbearing age with SAD to understand and choose appropriate and appropriate contraceptive methods. The method used in this service is a Focus Group Discussion (FGD) on women of childbearing age partners with SAD. The results of the analysis using the T test obtained a p-value of 0.000 which means that after assistance with family planning program socialization interventions, demonstrations and counseling on the selection of contraceptives there was an increase in knowledge, attitudes, and practices among women of childbearing age couples participating in family planning.Keywords: Indigenous community, contraception, empowerment.